Tradisi Kemponan dan Jappe’ dalam Masyarakat Melayu Sambas Kalimantan Barat - Reza Akbar; U. Sulia Sukmawati (LP2M IAIN Palangka Raya, 2019)
The people of Sambas Regency recognize the Kemponan belief. It is the belief about a disaster that can occur to someone if they reject the food or drink offered without tasting the food known as Jappe’. This study is to identify the Kemponan tradition and Jappe spreading out at the people of Sambas Malay. This study is qualitative field research using data collection methods through in-depth interviews. Dealing with the Kemponan and Jappe ’traditions, the Sambas Malay people is divided into four groups; those who believe and carry out both traditions, those who doubt the Kemponan and continue to carry out the Jappe’ tradition, those who do not believe in the existence of Kemponan but still carry out the Jappe' tradition, and those who have left the two traditions. The Kemponan and Jappe ' traditions viewed from a sharia perspective were that, first, it was allowed if Kemponan was only interpreted as a desire that was not conveyed and was not associated with the existence of magical power. Second, it was forbidden if it was believed that certain foods have the pulling power of the Kemponan and Jappe' and it was done to avoid calamity.